Artificial Intelligence Usage for Teaching and Learning of Christian Religious Education in Tertiary Institutions in Abuja, Nigeria - Steve Orseer Akullah; Nuhu Dantani (Researchparks Publishing, 2023)
The study assessed the perception of undergraduate students on Artificial Intelligence usage for teaching and learning of Christian Religious Education in tertiary Institutions in Abuja, Nigeria. Survey research design was adopted in this study. The multi-stage sampling technique was used to select the sample. Two out of the three public tertiary institutions in Federal Capital Abuja, Nigeria were randomly selected for the study. 260 undergraduate students were selected for the study randomly. A self-constructed questionnaire was used to gather data for the study. The questionnaire was titled “Perception of Undergraduate Students on Artificial Intelligence Usage for Teaching and Learning of CRS in Tertiary Institutions Questionnaire” (PUSALUTLQ). The instruments were validated using Face validity method. The reliability of the instrument was ascertained using Test-retest method. The data collected from the subjects on two occasions of administering the instruments were correlated using Pearson product moment correlation statistics and the reliability coefficients were found to be 0.76 to 0.78 r-values. Pearson product moment correlation statistics (r) were used to analyze the three hypotheses. The result obtained led to the conclusion that Artificial Intelligence can be used for implementation of teaching and learning of CRS in tertiary Institutions. Artificial Intelligence can be used to carry out researches in Christian Religious Education in tertiary Institutions. Artificial Intelligence can aid in the provision of community services by Christian Religious Education lecturers to the host communities were the tertiary institutions are located. Based on tis findings, the paper recommended that federal government should increase funding of tertiary institutions to enable the institutions acquire modern Artificial intelligence to aids implementation of teaching and learning of Christian Religious Education in tertiary institutions. Tertiary institutions administrators should ensure conducive environment are provided for the smooth operation of Artificial intelligence in tertiary institutions in Abuja, Nigeria.